2020
DOI: 10.1002/cti2.1136
|View full text |Cite
|
Sign up to set email alerts
|

Detection of IgM and IgG antibodies in patients with coronavirus disease 2019

Abstract: Objectives. This study aimed to determine the IgM and IgG responses against severe acute respiratory syndrome coronavirus (SARS-CoV)-2 in coronavirus disease 2019 (COVID-19) patients with varying illness severities. Methods. IgM and IgG antibody levels were assessed via chemiluminescence immunoassay in 338 COVID-19 patients. Results. IgM levels increased during the first week after SARS-CoV-2 infection, peaked 2 weeks and then reduced to near-background levels in most patients. IgG was detectable after 1 week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
323
3
21

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(378 citation statements)
references
References 21 publications
31
323
3
21
Order By: Relevance
“…Similar to a recent study [30] , we found that the antibody positivity rate was not signi cantly different between severe and non-severe patients with COVID-19. Our data showed that positive rates of IgG and IgM were 69.1% and 5.5%, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to a recent study [30] , we found that the antibody positivity rate was not signi cantly different between severe and non-severe patients with COVID-19. Our data showed that positive rates of IgG and IgM were 69.1% and 5.5%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, recovered patients had lower positive rates of IgM in this study. IgG is produced later than IgM and is typically maintained at a high level for 2 months [30] . Therefore, the levels of IgG and IgM can roughly re ect the disease stage.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24] Because of their convenience and cost-efficiency, new serological assays of IgG and IgM antibodies have been recognised as a promising diagnostic tool to complement viral nucleic acid screening in the atrisk populations. 25 Of note, IgG/IgM seroconversion can be observed in many patients after their infections with SARS-CoV-2, 4,18,20,23,26 and serological responses are associated with disease severity. 19 For instance, an observational study of 32 critically ill and 141 noncritically ill patients reported IgM and IgG seroconversion rates of 82.7% and 64.7%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Studies found that IgG and IgM have a good diagnostic value in the early stage of the disease [6][7][8]. However, the value of IgG and IgM in the diagnosis of cured COVID-19 patients is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…However, in patients with COVID-19, the relevance of IgM and IgG antibodies has not been clarified. Researches demonstrated that IgM and IgG could be identified during the early stage of COVID-19, and thus could have a high diagnostic value in patients with acute infection [6][7][8]. Compared with real-time reverse transcriptase polymerase chain reaction (RT-PCR), the detection of antibodies by ELISA is faster, less expensive, and easier to perform.…”
Section: Introductionmentioning
confidence: 99%